Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Secara Online Dalam Perspektif Ekonomi Islam : Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Siti Lamilatul Rofiah; A. Tarmizi; Mohammad Orinaldi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The rapid growth of information technology has created new business opportunities. The business opportunity in question is the existence of a trading system using internet media. The use of the internet for business transaction activities is known as electronic commerce (e-commerce). There are several factors that influence consumer considerations in making purchasing decisions online, one of these factors is price, product quality, and convenience. The purpose of this study was to find out whether there is a significant effect of price, product quality, and convenience on online purchasing decisions for students of the Faculty of Economics and Islamic Business, State Islamic University of Sultan Thaha Saifuddin Jambi. As well as to find out how Islamic economics reviews online purchasing decisions for students of the Islamic Faculty of Economics and Business at the State Islamic University of Sultan Thaha Saifuddin Jambi. The method used in this research is a quantitative method. The research sample consisted of 85 students using a sampling technique, namely purposive sampling. The results of this study indicate that there is one variable that has a positive and significant effect on online purchasing decisions, namely convenience, while the other 2 variables, namely price and product quality, have no significant effect on online purchasing decisions. Simultaneously, there is a significant influence between price, product quality, and convenience on online purchasing decisions. the R Square value is 0.768 or 76.8%, which means that the influence of the independent variables on the dependent variable has an effect of 76.8% and the remaining 23.2% is influenced by other variables outside this study. The Islamic economic view regarding online purchasing decisions is permissible as long as there are no elements of usury, fraud, tyranny, or the goods are defective.